Model Pemilihan Rekanan Strategis Penyedia Peralatan Pabrik Gula dengan Penerapan Metode Fuzzy dan Analytical Network Process (Studi di PT Kebon Agung, Surabaya) - Basuki, Dwi Tjahjono; Rahayu, Mintarti; Sumiati, Sumiati (Jurnal Aplikasi Manajemen, 2008)
The Government of Indonesia through its policies motivate national sugar industry for revitalization in order to increase efficiency and industrial productivity due to competition. Follow and support Government policies, PT Kebon Agung expand capacity of its sugar factories. The expand of production capacity explain in a program named PPKA (Program Pengembangan PT Kebon Agung) which has time from 2005 until 2011. In this time the company has bought many machines and equipments for process production. Strategic Supplier selection of machine and production equipment is not easy and has highly risk, cause if failure happen it will be harm competitive advantage in the future. This study provide a model for strategic supplier selection of equipment sugar factory which is mill. This model use Fuzzy and Analytical Network Process Methods. For the criteria this study refer Diksons vendor selection criteria and Hierarchical approach to choice of technologies. Result of this study appointed PT Barata Indonesia as the top rank and the list of rank important criteria is easy to maintenance, material, availability spare part. repair service, complain procedures and otomatization.